Investigation of the Fe doping effect on the B-site of the layered perovskite PrBa0.8Ca0.2Co2O5+δ for a promising cathode material of the intermediate-temperature solid oxide fuel cells. (8th January 2019) - Lim, Chaehyun; Sengodan, Sivaprakash; Jeong, Donghwi; Shin, Jeeyoung; Kim, Guntae
Abstract: Layered perovskites can be considered as promising cathode materials for intermediate-temperature solid oxide fuel cell because of their fast oxygen kinetics compared to simple perovskites. Among them, the cobalt-based layered perovskites are considered as very promising cathode materials due to its high conductivity and fast oxygen kinetics, but they are unstable under operating condition. Doping other transition metal such as Fe, Mn, Cu, and Ni can be considered to solve the instability of the cobalt-based layered perovskites. In this paper, we investigated Fe doped cobalt-based layered perovskite, PrBa0.8 Ca0.2 Co2- x Fe x O5+ δ ( x = 0, 0.5, and 1.0), as prospective cathode materials in terms of their crystal structures, thermal expansion behavior, electro- and electro-chemical properties. The PrBa0.8 Ca0.2 Co1.5 Fe0.5 O5+ δ shows improved maximum power density of 1.89 W cm −2 and polarization resistance of 0.080 Ω cm 2 at 600 °C as compared with un-doped PrBa0.8 Ca0.2 Co2 O5+ δ while maintaining suppressed thermal expansion. Based on these results, PrBa0.8 Ca0.2 Co1.5 Fe0.5 O5+ δ can be considered as a promising cathode material for intermediate-temperature solid oxide fuel cell. Highlights: Electrochemical properties and stability of the Ca doped PrBaCo2 O5+ δ can be improved by Fe doping. The stronger [Fe–O] bonding strength increases the mobile oxygen species in the Ln-O layer of layered perovskites. The increased mobile oxygen improves the catalytic activity and thermal stability. Fe doped PrBa0.8 Ca0.2 Co2 O5+ δ can be considered as a promising cathode material.